Peran Perempuan Pedagang Kaki Lima Dalam Meningkatkan Ketahanan Keluarga (Studi Kasus Perempuan Pedagang kaki lima di UIN KHAS Jember) - Siti Aisah; Naili Ziana Zakiyah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Street vending is a business carried out by someone with the aim of earning additional income or indeed becoming the main source of income in a family. Around the UIN KHAS Jember campus there are many street sellers, where apart from men there are also female street sellers, if If a married woman runs a business, the woman will also carry out two tasks, namely as a housewife and also a business person, so the aim of this research is to find out what strategies are used by female street vendors in maintaining family resilience, the impact of being busy business and relationships with family and how they share their time with family. The type of research method used is qualitative research methods. Based on the results of research that has been conducted, it is clear that: (1) The majority of female street vendors work because of relatively low family economic factors. (2) The role of women as street vendors contributes a lot to improving the family's economy, the income they earn is quite higher than their husband's income. This makes women have a dual role in the family, namely they are housewives and also the backbone of the family.